The Influence Of Work Environment And Work Discipline On Employee Performance At Makida Collection Tasikmalaya - Ilham, Bintang Triyuana; Rahwana, Kusuma Agdhi; Risana, Dudu (CV. Utami, 2024)
The research aims to determine the influence of the work environment and work discipline on employee performance at Makida Collection Tasikmalaya. The method used is a quantitative approach with a research sample of 40 respondents from the production/sewing department of Makida Collection Tasikmalaya employees. The types of data used in this research are primary and secondary data. The data analysis tool in this research uses a multiple linear regression analysis tool using SPSS version 25. The research results show that the Work Environment and Work Discipline simultaneously have a significant effect on Employee Performance. The work environment partially has a significant effect on employee performance. Work Discipline partially has a significant effect on Employee Performance.